2002
DOI: 10.1001/archneur.59.3.418
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin A Treatment for Primary Hemifacial Spasm

Abstract: Treatment with BTX effectively induces sustained relief from symptoms of HFS in the long term, with only minimal and transient adverse reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
91
3
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(107 citation statements)
references
References 10 publications
(7 reference statements)
5
91
3
8
Order By: Relevance
“…16,25,29,36,45,56 Little work has been done to track longer-term outcomes in terms of response rates, duration of improvement, and long-term adverse reactions. 28,40,47,57,58 In our long-term, multicentre study, we have obtained at least a 96% response rate and a mean duration of improvement of 18, 21, and 14 weeks for BEB, HFS, and EN, respectively. This outcome compares well with shorter-term study results.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…16,25,29,36,45,56 Little work has been done to track longer-term outcomes in terms of response rates, duration of improvement, and long-term adverse reactions. 28,40,47,57,58 In our long-term, multicentre study, we have obtained at least a 96% response rate and a mean duration of improvement of 18, 21, and 14 weeks for BEB, HFS, and EN, respectively. This outcome compares well with shorter-term study results.…”
Section: Discussionmentioning
confidence: 86%
“…We found that anxiety was more frequent in the HFS patient group (P ¼ 0.045), emphasizing the need for treatments such as BoNT-A injections, which have showed to improve the quality of life and reduce the severity of depressive symptoms in patients with blepharospasm. 46 Some potential limitations of our study include the retrospective nature of our analysis and the use of a patient self-evaluation scale, which have earlier been used effectively, 58 rather than an observer-based rating to determine the effect of BoNT-A treatment on BEB, HFS, and EN patients. However, the large effect reported in other studies (over 90% of patients benefit) makes it difficult and probably unethical to perform controlled trials for the efficacy of BoNT-A.…”
Section: Discussionmentioning
confidence: 99%
“…Outros trabalhos, no entanto, não observaram mudança em relação à eficácia ou necessidade de aumento da dose da medicação no seguimento em longo prazo (10)(11)(12)(13) . Por outro lado, a manutenção do tratamento periódico poderia diminuir a dose necessária para controle do espasmo facial.…”
Section: Discussionunclassified
“…O tratamento sintomático não invasivo mais eficaz do espasmo hemifacial consiste em injeções de toxina botulínica tipo A em intervalos de três a quatro meses conforme a resposta clínica 1,8,20,21 . A melhora sintomática dura em média 12 semanas 20,21 .…”
Section: Discussionunclassified
“…A melhora sintomática dura em média 12 semanas 20,21 . Efeitos colaterais como ptose, lagoftalmo e inversão do lábio superior são transitórios e estão relacionados com maior difusão da droga para áreas pró-ximas e com a dose utilizada.…”
Section: Discussionunclassified